2001
DOI: 10.1007/s004250100522
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic electron transport adjustments in overwintering Scots pine ( Pinus sylvestris L.)

Abstract: As shown before [C. Ottander et al. (1995) Planta 197:176-183], there is a severe inhibition of the photosystem (PS) II photochemical efficiency of Scots pine (Pinus sylvestris L.) during the winter. In contrast, the in vivo PSI photochemistry is less inhibited during winter as shown by in vivo measurements of deltaA820/A820 (P700+). There was also an enhanced cyclic electron transfer around PSI in winter-stressed needles as indicated by 4-fold faster reduction kinetics of P700+. The differential functional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
99
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 43 publications
(50 reference statements)
16
99
0
Order By: Relevance
“…It has been revealed by thermoluminescence measurements that narrowing the temperature gap (∆T M ) between S 2/3 Q Band S 2 Q A -charge recombinations increases the probability for an alternative non-radiative P680 + Q Aradical pair recombination pathway for energy dissipation within the reaction centre of PSII (reaction center quenching) (Sane et al, 2002Ivanov et al, 2003Ivanov et al, , 2005Ivanov et al, , 2006. Indeed, reaction center quenching of excess light was suggested to play substantial role in supplementing the antenna based NPQ in cold acclimated Scots pine (Ivanov et al, 2001) and cold hardened Arabidopsis and barley plants (Ivanov et al, 2006) when the enzymatic conversion of violaxanthin to zeaxanthin within the xanthophyll cycle is thermodynamically restricted by low temperatures. In addition, it has been demonstrated that not only shifts to lower temperatures, but exposure to increased "excitation pressure", i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed by thermoluminescence measurements that narrowing the temperature gap (∆T M ) between S 2/3 Q Band S 2 Q A -charge recombinations increases the probability for an alternative non-radiative P680 + Q Aradical pair recombination pathway for energy dissipation within the reaction centre of PSII (reaction center quenching) (Sane et al, 2002Ivanov et al, 2003Ivanov et al, , 2005Ivanov et al, , 2006. Indeed, reaction center quenching of excess light was suggested to play substantial role in supplementing the antenna based NPQ in cold acclimated Scots pine (Ivanov et al, 2001) and cold hardened Arabidopsis and barley plants (Ivanov et al, 2006) when the enzymatic conversion of violaxanthin to zeaxanthin within the xanthophyll cycle is thermodynamically restricted by low temperatures. In addition, it has been demonstrated that not only shifts to lower temperatures, but exposure to increased "excitation pressure", i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thermoluminescence (TL) measurements of intact WT and F2 mutant barley leaves were performed on a personal-computer-based TL data acquisition and analysis system as described earlier (Ivanov et al, 2001). A xenon-discharge flash lamp (XST103, Heinz Walz GmbH, Effeltrich, Germany) was used to expose the samples to a single turnover flash (1.5 ms peak width at 50% of maximum).…”
Section: Thermoluminescence Measurementsmentioning
confidence: 99%
“…Increased photorespiration has previously been shown to be an effective photoprotective strategy in high mountain plants under low temperature (Streb et al, 1998). Ivanov et al (2001) suggested that cyclic electron transport around PSI is necessary to dissipate excess energy and to retain functionality of the photosynthetic apparatus in winter-stressed pine needles. Our observation of a significant increase in b-carotene in SD/HT (Fig.…”
Section: Acclimation Of Photosynthetic Energy Conversion and Compositmentioning
confidence: 99%
“…Overwintering evergreen conifers seem to be able to shift between the dynamic and the sustained antenna quenching (q O ) modes for dissipating excess energy . Aside from NPQ of excess energy in the antenna, a zeaxanthin independent way of quenching has been described in the reaction center (RC; Ivanov et al, 2001Ivanov et al, , 2006Lee et al, 2001;Sane et al, 2003;Finazzi et al, 2004). In addition to antenna and RC quenching, excess energy can be funneled into a range of alternative electron sinks, most notably photorespiration (Osmond and Grace, 1995;Streb et al, 1998), the water-water cycle (Asada, 1999), and cyclic electron transport (Ivanov et al, 2001;Kanervo et al, 2005).…”
mentioning
confidence: 99%
“…Given the evergreen nature of their needles, conifers must employ mechanisms to protect their photosynthetic apparatus during severe winters and recover their capacity for photosynthesis during the subsequent spring (Yamazaki et al, 2003;Zarter et al, 2006aZarter et al, , 2006b). Several photoprotective mechanisms have been invoked as preventing photodamage of the photosynthetic apparatus in overwintering evergreens, including (i) enhanced cyclic electron transport around photosystem I (Huner et al, 1988;Ivanov et al, 2001;Ö quist and Huner, 2003), (ii) degradation of key photosystem II proteins (D1 and the oxygen evolving complex) to inhibit superoxide formation (Ottander et al, 1995;Adams et al, , 2006Zarter et al, 2006aZarter et al, , 2006bZarter et al, , 2006c, and (iii) sustained engagement of the carotenoids zeaxanthin and antheraxanthin in continuously high levels of photoprotective energy dissipation, resulting in sustained low PSII efficiency, during the winter Demmig-Adams, 1994, 1995;Adams et al, , 2002Adams et al, , 2006Verhoeven et al, 1996Verhoeven et al, , 1998Adams and Barker, 1998). It has also been reported that, in zeaxanthin-free isolated major light-harvesting complexes (LHCII), neoxanthin Ilioaia et al, 2011;Zubik et al, 2011) and lutein (Ilioaia et al, 2011;Jahns and Holzwarth, 2012;Wahadoszamen et al, 2012) are able to quench fluorescence and thus facilitate 238 / ARCTIC, ANTARCTIC, AND ALPINE RESEARCH ᭧ 2013 Regents of the University of Colorado 1523-0430/6 $7.00 thermal energy dissipation (Ilioaia et al, 2011;Ruban et al, 2012).…”
Section: Introductionmentioning
confidence: 99%